Functional properties of photo-crosslinkable biodegradable polyurethane nanocomposites. (August 2020) - Salgado, Cástor; Arrieta, Marina P.; Sessini, Valentina; Peponi, Laura; López, Daniel; Fernández-García, Marta
Abstract: Smart and functional properties of coumarin and PCL-based polyurethane (PU) nanocomposites reinforced with both pristine silica nanoparticles and silica nanoparticles modified with coumarin, have been studied. Coumarin is a photo-responsive derivative, which induces photo-crosslinking when it is incorporated in the PU moieties. Swelling measurements were performed to study the photo-crosslinking fraction and the results are in concordance with the degree of crosslinking (DC) calculated by UV measurements. Shape memory behavior was studied by thermo-mechanical cycles, by measuring the strain recovery and shape fixity ratios of the photo-crosslinked films. The modification of silica nanoparticles allows an improvement in the dispersion of the reinforcements into the PU matrix, which leads to an enhancement of the shape memory properties. Finally, the materials were disintegrated under composting conditions at laboratory scale level to confirm their biodisintegrable behavior. Graphical abstract: Image 1 Highlights: Functional polyurethanes based on poly-e-caprolactone and coumarin have been evaluated as coatings. Photo-crosslinking degree was measured by swelling and the results are in concordance with UV measurements. The incorporation of coumarin-functionalized silica nanoparticles leads to a enhancement of the shape memory performance. The nanocomposites were completely disintegrated after 14 days under composting conditions.